1999
DOI: 10.1046/j.1365-2826.1999.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Pharmacological Characterization of Two Functional Splice Variants of Corticotropin‐Releasing Factor Type 2 Receptor from Tupaia belangeri

Abstract: From brain, heart and muscle tissue of the tree shrew (Tupaia belangeri), a higher order mammal, cDNA clones were isolated that encoded two functional splice variants of the corticotropin-releasing factor (CRF) type 2 receptor (CRF-R2). The first, full-length splice variant, amplified from brain and heart tissue, encoded a CRF receptor protein that is 410 amino acids in length and approximately 96% homologous to human CRF-R2alpha. The second, full-length splice variant, derived from skeletal muscle tissue, enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 57 publications
0
44
0
4
Order By: Relevance
“…Complementary DNAs for the CRF 2 receptor have been isolated from man (Liaw et al, 1996;Valdenaire et al, 1997;Kostich et al, 1998), tree shrew (Palchaudhuri et al, 1999), rat (Lovenberg et al, 1995b), mouse (Kishimoto et al, 1995;Perrin et al, 1995;Stenzel et al, 1995), frog (Dautzenberg et al, 1997), and fish (Arai et al, 2001;Pohl et al, 2001). Three functional splice variants (Lovenberg et al, 1995b;Kostich et al, 1998) and a truncation variant (Miyata et al, 1999) have been identified for the mammalian CRF 2 receptor.…”
Section: The Corticotropin-releasing Factor Type 2 Receptormentioning
confidence: 99%
“…Complementary DNAs for the CRF 2 receptor have been isolated from man (Liaw et al, 1996;Valdenaire et al, 1997;Kostich et al, 1998), tree shrew (Palchaudhuri et al, 1999), rat (Lovenberg et al, 1995b), mouse (Kishimoto et al, 1995;Perrin et al, 1995;Stenzel et al, 1995), frog (Dautzenberg et al, 1997), and fish (Arai et al, 2001;Pohl et al, 2001). Three functional splice variants (Lovenberg et al, 1995b;Kostich et al, 1998) and a truncation variant (Miyata et al, 1999) have been identified for the mammalian CRF 2 receptor.…”
Section: The Corticotropin-releasing Factor Type 2 Receptormentioning
confidence: 99%
“…The splice variants have a common 377 amino acid C-terminal part, whereas the extreme N-termini, which are encoded by one or two exons (Dautzenberg and Hauger, 2002), differ substantially from one another. The CRH 2α receptor, a 411-413 amino acid protein, has been isolated from mammalian and amphibian species (Dautzenberg et al, 1997) (Palchaudhuri et al, 1999). In contrast, CRH 2β receptors, which are 430-438 amino acids in size, have only been reported in mammals (Kishimoto et al, 1995) (Palchaudhuri et al, 1999) (Valdenaire et al, 1997).…”
Section: Crh Receptorsmentioning
confidence: 99%
“…The CRH 2α receptor, a 411-413 amino acid protein, has been isolated from mammalian and amphibian species (Dautzenberg et al, 1997) (Palchaudhuri et al, 1999). In contrast, CRH 2β receptors, which are 430-438 amino acids in size, have only been reported in mammals (Kishimoto et al, 1995) (Palchaudhuri et al, 1999) (Valdenaire et al, 1997). Finally, the 397 amino acid CRH 2γ receptor is exclusively found in humans (Kostich et al, 1998) (Palchaudhuri et al, 1999).…”
Section: Crh Receptorsmentioning
confidence: 99%
See 2 more Smart Citations